Coordination of Noble Metals in Poly(vinyl mercaptoethanol) Particles Prepared by Precipitation/Emulsion Polymerization. Issue 3 (1st January 2023) - Ziegenbalg, Nicole; Ulrich, Hans F.; Stumpf, Steffi; Mueller, Philipp; Wiethan, Jürgen; Danner, Janette; Schubert, Ulrich S.; Adermann, Torben; Brendel, Johannes C.
Abstract: S ‐Vinyl monomers react readily in radical polymerizations resulting in polymers with interesting features such as enhanced refractive indices, increased thermal stability, or the ability to coordinate various metals. Among them, vinyl mercaptoethanol (VME) can be produced in industrial scale, but the poor solubility of the resulting homopolymer limits its application. In this contribution, polymerizations of the monomer are investigated in water forming a heterogeneous system. The good solubility of the monomer in water imparts the system with mixed characteristics between a precipitation and an emulsion polymerization. Evaluating various surfactants, only polyvinyl alcohol (PVA) is found to create stable dispersions, although micrometer‐sized particles are formed with a broad size distribution. Nevertheless, the particles are able to coordinate silver or gold ions. Attempts to reduce the noble metal ions by commercial reducing agents fail. However, exposure to sunlight unexpectedly results in a controlled reduction of the metal ions and the formation of composite particles. Silver ion‐containing dispersions demonstrate strong antibacterial properties, while the effect is diminished in the corresponding composite. Overall, the precipitation/emulsion polymerization of VME represents a promising pathway to stable sulfur‐rich polymer dispersions with the ability to coordinate metal ions or form reactive metal composites. Abstract : The good solubility of vinyl mercaptoethanol (VME) in water enables direct access to sulfur‐rich polymer dispersions by radical polymerization in a mixed emulsion/precipitation process using polymeric stabilizers. The resulting particles are capable of coordinating noble metal salts, which can simply be reduced by sunlight to create dispersed polymer nanocomposites of the corresponding metals.